PENINGKATAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) MELALUI PENGUATAN IKLIM ORGANISASI DAN ADVERSITY QUOTIENT - Baban Sobandi; Nandang Hidayat; Sutji Harijanto (JURNAL MANAJEMEN PENDIDIKAN, 2021)
IMPROVING ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) THROUGH STRENGTHENING ORGANIZATIONAL CLIMATE AND ADVERSITY QUOTIENTOrganizational Citizenship Behavior (OCB) of teachers is an important behavior possessed by teachers that related in achieving the goals of school organizations and the national education system. However, the results of the preliminary survey indicated that teachers' OCB was still needed to be improved. The aim of this study was identifying a number of concrete efforts that might be implemented to improve the OCB which were concluded based on the results of the causal relationship analysis between:1) Organizational Climate and Organizational citizenship behavior (OCB) of teachers. 2) Adversity Quotient with Organizational citizenship behavior (OCB) teachers. 3) Organizational Climate and Adversity quotient altogether with Organizational citizenship behavior (OCB) teachers. This research was an empirical study using correlational approach and SITOREM analysis on non-civil servant of the state high school teachers at the Cibadak Commissariat, Sukabumi Regency. The population in this study was 148 teachers  with a sample of 108 respondents who were pointed out by using the Proportional Random Sampling technique. Hypothesis testing was carried out using parametric statistical analysis in the form of simple and multiple linear regression analysis, simple, multiple, and partial correlation analysis with a significance level of a = 0.01 and a = 0.05. This study resulted in three conclusions. First, there was a very significant positive relationship between organizational climate variables (X1) and organizational citizenship behavior (Y) where the correlation coefficient value (ry1) was 0.48 and supported by the regression equation = 87.031+0.336 X1. The contribution of X1 to Y was 23.4% as indicated by the coefficient of determination (ry1)2 of 0.234. Second, there was a significant positive relationship between adversity quotient (X2) and organizational citizenship behavior (Y) where the correlation coefficient (ry2) was 0.238 and supported by the regression equation = 98.001 + 0.236X2. The contribution of X2 to Y was 5.68% which was indicated by the coefficient of determination (ry2)2 as 0.056. Third, there was a very significant positive relationship between organizational climate (X1) and adversity quotient (X2) with organizational citizenship behavior (Y) where the correlation coefficient (ry1.2) was 0.44 and supported by the regression equation = 87.790+ 0.322X1 + 0.04 X2. The contribution of organizational climate (X1) and adversity quotient (X2) to Y was 19.7%, which was indicated by the coefficient of determination (ry1.2)2 as much as 0.197.